2021
DOI: 10.1002/jez.b.23113
|View full text |Cite
|
Sign up to set email alerts
|

Resolving between novelty and homology in the rapidly evolving phallus of Drosophila

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 81 publications
2
13
0
Order By: Relevance
“…We see no connection between the base of the pregonites and the claws (figure 1d,e), which confirms that the claws are not 'basal extensions' of the pregonites evident in allied species of the D. ananassae complex [21,25]. The postgonal sheath (sensu [19]) folds and bends freely, and is bilaterally symmetrical, lobe-like and 'cloaks' the claws dorsally (figure 2a-d).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…We see no connection between the base of the pregonites and the claws (figure 1d,e), which confirms that the claws are not 'basal extensions' of the pregonites evident in allied species of the D. ananassae complex [21,25]. The postgonal sheath (sensu [19]) folds and bends freely, and is bilaterally symmetrical, lobe-like and 'cloaks' the claws dorsally (figure 2a-d).…”
Section: Resultssupporting
confidence: 53%
“…Our results provide observational and direct experimental evidence contradicting it: the evidence supports sperm transfer occurring via the route described for other Drosophila, that is, from the aedeagus into the reproductive tract via the female gonopore. Recently, Rice et al [19] showed that the claws have a distinct developmental origin, deriving from the lateral portions of the central primordium of the phallus observable during pupal metamorphosis. Since most cells of the central primordium normally give rise to the aedeagus, the term aedeagal lateral processes for the claw-like structures was proposed [19], a term we adopt here and use interchangeably with 'claws'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed the presence of Svb in the inner cavity of the developing ovipositors of D. melanogaster and the sha expression in the similar regions of D. suzukii and D. subpulchrella , suggesting that the network is also utilized to develop the ovipositor trichomes. Taken together, in parallel to the well-documented cases of rapidly evolving genital structures in Drosophila males (e.g., [ 42 45 ]), our study opens an opportunity to explore the evolution of a rapidly diversifying morphological trait of the female genitalia. Our study also highlights the gene regulatory network of a functionally distinct and divergent trichome system associated with ecological niche exploitation.…”
Section: Discussionsupporting
confidence: 57%
“…For this reason, they are excellent candidates for genetic and developmental investigations of novel traits. As an example, diverse genital morphologies are present in species of Drosophila , and the rapid pace of genital evolution has often been attributed to conflict between the sexes [18], [19], [21]. Drosophila eugracilis ( D .…”
Section: Introductionmentioning
confidence: 99%